THE RIGHT TO INCLUSIVE EDUCATION AS A SUBJECTIVE RIGHT FOR PERSONS WITH DISABILITIES - Khaydarova Khilola Anvarovna (Bright Mind Publishing, 2025)
The article examines the right to inclusive education as a subjective right of persons with disabilities. International and national legal frameworks for ensuring the right to inclusive education are analyzed. Special attention is paid to the role of inclusive education in integrating persons with disabilities into society and ensuring equal access to education. The main principles and mechanisms for implementing the right to inclusive education are considered.
Keywords: inclusive education, human rights, persons with disabilities, right to education, equal access to education, educational integration.